Activités de formation des enseignants novices et trajectoire de satisfaction professionnelle : conceptualisation et illustration - Jérôme Amathieu; Sébastien Chaliès (Activités)
As in other professional fields, there would seem to be a consensus regarding links that can be established between teachers’ health and the nature of their activities in the workplace. From the activity theory standpoint, this consensus leads to one main restriction. By equating job satisfaction with a stable and “situated” psychological state, these studies dissociate it, so to speak, from the actual activity of teaching one that is necessarily situated in a class context and thus constantly subject to circumstances and changing situations. Based on these postulates, borrowed from a research program conducted in cultural anthropology (Auteurs, 2017), this study aims to help overcome this issue. To this end, we successively propose (i) an original theoretical conceptualization that makes it possible to apprehend, from a qualitative point of view, the coupling between activity and professional satisfaction, (ii) a methodological approach to account for the location and dynamic nature of this coupling and (iii) an illustration and discussion of the heuristic nature of these theoretical and methodological propositions based on the presentation of empirical results extracted from a case study.